DETERMINATION OF FORECASTING TECHNICAL AND ECONOMIC INDICES EXPLOITATION UNDERGROUND WATER FOR EMPIRICAL RELATIONSHIPS - Shevchenko, O.; Koshliakov, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The aim of the work is to establish internal links between the technical and economic indicators of the operation of groundwater deposits, to analyze current actual data, to find ways to determine and unify the calculations of the unit price of finished goods, the subsoil use tax, the profitability factor for cases when the majority of the necessary initial parameters are not determined; to discuss the method of determining the tax for the use of subsoil, since the essence of the tax does not correspond to its name. Results. Two approaches to the calculation of the tax for the use of subsoil have been developed: 1) by determining the price of a unit of commodity output through the profitability coefficient, then – the gross income, and then by calculating the tax using the coefficients established by the NKU; 2) through empirical relationships between the target value of the tax and the value of gross costs (the dependencies are established when processing the actual data for a number of enterprises-subsoil users of Ukraine). The coefficient of profitability is recommended to be defined as the ratio of the long-term (over 25 years) taxable profit of the enterprise to the average annual gross costs. The characteristic ratios of working capital, fixed assets and production funds are established, and real values of profitability for various groups of enterprises are given. An analysis of the profitability of enterprises shows that in 72 % of cases the net profit is less than the amount of taxes that go to the state. For enterprises that extract mineral waters and use them for bottling, the share of circulating assets in production lies in the range of 63 ... 76 %, and their ratio to fixed assets ranges from 1,7 to 3,3. It is established that the rental payment for the use of subsoil amounts to about 4,1% of gross expenditure, taking into account the coefficient of 0,7: КН Е П 0,0 вал 41 = × . If the coefficient at вал Е reaches 0,06 this indicates that the coefficient 0,7 is not taken into account when calculating the tax. Practical significance. The revealed links between economic indicators and the patterns of distribution of indicators for various groups of subsoil users have made it possible to simplify the calculation of important indicators of profitability. Found algorithms for calculating those indicators that are calculated by unknown forecast characteristics of the economic activity of the subsoil user will help the developers of feasibility studies optimize the calculations and minimize unjustified losses of the subsoil user. In addition, found empirical coefficients will help experts to detect errors when testing the feasibility study.